Using Image Processing Technique in Packaging Decoration - Zhiyuan, Li (2009)
For the past decades, the decoration of packaging plays an important role in promoting the product to the consumer, especially related to the fast moving consumer products. As the product decoration field had attracted much attention, there is a demand to strengthen its effect of decoration to packaging industry. Therefore, one of the active research studies in packaging decoration is to improve the clarity and special effect on the decoration image using image processing techniques. Currently, there has tremendous number of drawing package or computer-aided design software for aiding design in general, but none of them specifically built for packaging decoration purpose. The aim of this thesis is to develop an application for packaging decoration purpose that allow user to apply image processing algorithm onto the decoration image and subsequently paste the decoration image on a flat and curve surface in order the decoration image to be viewed at different angles. In order to validate the efficiency of the developed application to achieve the stated aims, two experiments are conducted on the collected 1000 decoration images. The analysis results concludes the developed application is successfully allow user to improve the quality of the appearance clarity of the decoration image by applying selected image processing algorithm and subsequently further verified the effect of the pasted decoration image on the surfaces of the packaging